2020
DOI: 10.1016/j.devcel.2020.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic-Independent Signaling via CHRNA2 Regulates Beige Fat Activation

Abstract: Highlights d CHRNA2 signaling in adipocytes mediates systemic energy homeostasis in vivo d Acute high fat diet feeding activates CHRNA2 signaling in beige adipocytes d CHRNA2 signaling regulates both UCP1-and creatinemediated pathways d CHRNA2 signaling regulates the activation of glycolytic beige adipocytes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 35 publications
1
24
1
Order By: Relevance
“…Interestingly, miR-182-5p deficiency had no effect on Ucp1 expression ( Supplemental Figure 6, B and C ) and macrophages’ polarization ( Supplemental Figure 6D ) in BAT of cold-exposed mice, indicating miR-182-5p plays a selective role in controlling thermogenic gene expression in beige fat but not in BAT. These results are consistent with the findings that both FGF21 ( 6 ) and the acetylcholine signaling pathway ( 25 ) have a major effect on beige but not BAT thermogenesis and that distinct mechanisms are present in WAT and BAT to regulate thermogenesis ( 23 , 26 , 27 ). How the tissue selectivity of miR-182-5p is established is unclear, but it is known that BAT has much lower numbers of macrophages compared with WAT ( 28 , 29 ).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, miR-182-5p deficiency had no effect on Ucp1 expression ( Supplemental Figure 6, B and C ) and macrophages’ polarization ( Supplemental Figure 6D ) in BAT of cold-exposed mice, indicating miR-182-5p plays a selective role in controlling thermogenic gene expression in beige fat but not in BAT. These results are consistent with the findings that both FGF21 ( 6 ) and the acetylcholine signaling pathway ( 25 ) have a major effect on beige but not BAT thermogenesis and that distinct mechanisms are present in WAT and BAT to regulate thermogenesis ( 23 , 26 , 27 ). How the tissue selectivity of miR-182-5p is established is unclear, but it is known that BAT has much lower numbers of macrophages compared with WAT ( 28 , 29 ).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, we saw no evidence that browning of ingWAT was mediated by a reduction in proinflammatory macrophages or the associated cytokines (e.g., TNFα), as has been suggested ( 41 , 42 ). Similarly, we saw no compelling evidence for the involvement of anti-inflammatory macrophages in the browning process in ingWAT where these macrophages have been suggested to play a mediatory role ( 14 17 , 20 , 21 , 28 , 29 , 43 ).…”
Section: Discussioncontrasting
confidence: 56%
“…Certain macrophages have also been suggested to be needed to maintain sympathetic innervation as such ( 27 ). In addition (or alternatively), anti-inflammatory macrophages have been suggested to release acetylcholine that would interact with cholinergic receptors on the brite/beige adipocytes themselves ( 28 , 29 ) and in this way stimulate thermogenic recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a glycolytic beige population was identified that could be induced by chronic cold adaptation in the absence of -adrenergic receptor signaling (Chen et al, 2019). Excess calorie intake also can trigger the activation of CHRNA2-dependent beige adipocytes (Jun et al, 2020), which also are glycolytic and -adrenergic signaling independent. Interestingly, Foxp4-inactivated beige adipocytes appeared to only react to cold exposure, not to an adrenoceptor agonist (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%